The effect of beta-elemene on alpha-tubulin polymerization in human hepatoma HepG2 cells - Zhang, Jielin; Mao, Yuqiu; Hou, Li; Cui, Xiaonan (Chinese Journal of Cancer Research; Vol 25, No 6 (December 26, 2013): Chinese Journal of Cancer Research, 2013)
Objective: To investigate the impact of beta-elemene injection on the growth and alpha-tubule of human hepatocarcinoma HepG2 cells. Methods: Cell proliferation was assessed by MTT assay. Cell cycle distribution was detected by flow cytometry (FCM). The mRNA expression of alpha-tubulin was measured by RT-PCR. Western blot analysis was used to determine protein expression of alpha-tubulin and the polymerization of tubulin. Results: Beta-elemene injection inhibited HepG2 cells proliferation in a dose- and time-dependent manner; FCM analysis indicated beta-elemene injection induced cell cycle arrested at S phase. RT-PCR and western-blot analysis showed that beta-elemene injection down-regulated alpha-tublin at both mRNA and protein levels, presenting a dose-dependent manner. Moreover, beta-elemene injection reduced the polymerization of microtubules in a dose-dependent manner. Conclusions: Beta-elemene injection can inhibit the proliferation of hepatoma HepG2 cells and induce cell apoptosis, the mechanism might be partly related to the down-regulation of alpha-tubulin and inhibition of microtubular polymerization.